Strategies Promoting Dialogic Talk during Cooperative Learning : Cooperative Learning - Gillies, Robyn M. (Autonomy and Responsibility Journal of Educational Sciences, 2023)
The role of talk in the construction of knowledge and learning has gathered interest in recent years as studies have been published that demonstrate the importance of social interaction in promoting cognitive development and academic learning. While there is a large volume of research that attests to the benefits that students derive when they work cooperatively together, it is only in the last 30 years that studies have been published that demonstrate how students learn by interacting with others and how teachers can utilise this information to create classroom experiences to ensure these benefits are realised. This article discusses the role of dialogic talk during cooperative learning and its capacity to promote students’ thinking and learning. The article provides insights into how one teacher used dialogic talk in her classroom to promote student interactions, thinking and learning. It also provides an example of how students in one small group listened to each other, asked questions, sought clarifications, and provided reasons and justifications for their suggestions as they considered the perspectives of others on how to construct an earthquake proof building.